Lived Religion as a Pedagogical Ecology for Early Childhood Character Formation in Muslim Families - Qusyairi, A. Imam; Aisah, Siti; Halid, Ahmad (Al-Athfal: Jurnal Pendidikan Anak, 2026)
Purpose – This manuscript conceptualizes lived religion in Muslim families as a pedagogical ecology for early childhood character formation. It explains how practices, relationships, routines, objects, narratives, and community participation shape children’s moral and social-emotional development and inform early childhood education.Design/methods/approach – A selective critical review examines literature on lived religion, ecological and sociocultural theories, religious socialization, children’s spirituality, character education, and Islamic early childhood education. Sources were purposively selected for relevance to family practices, learning mechanisms, and character education. Analysis involved close reading, comparison, and conceptual synthesis. Rather than systematically mapping evidence, the review develops an argumentative framework for empirical testing.Findings – This conceptual synthesis proposes that early childhood religiosity and character can be understood through the everyday rhythms of family life. Prayer, greetings, manners related to eating and sleeping, prophetic stories, emotional exemplarity, religious material space, and community participation emerge as the most salient forms of practice. These practices operate through situated modelling, rhythmic habituation, experience-bound moral narratives, meaning-based emotion regulation, and social recognition within communities of value. These five mechanisms are heuristic; therefore, they need to be read alongside relationship quality, emotional security, child agency, and the cultural variation of Muslim families.Research implications/limitations – The framework does not represent all Muslim families across Global South contexts. As a selective critical review, it supports conceptual synthesis but cannot replace ethnographic observation, family interviews, or fieldwork. Further research should examine variation by social class, culture, parental education, rural–urban setting, and educational resources.Practical implications – Teachers can use family religious practices as entry points for character education connected to children’s lives. Religious values may be explored through play, stories, dialogue, art, activities, and narrative observation. Educators should avoid imposing standards of piety or judging families against norms. Collaboration among teachers, parents, and communities is essential for inclusive, culturally responsive, and developmentally appropriate learning.Originality/value – The ecology of everyday piety framework positions Muslim family religious practices as pedagogical resources for character formation. It connects lived religion with moral, social-emotional, and character development through routines, relationships, stories, objects, and community practices. The framework extends character education beyond formal schooling and offers a context-sensitive approach for diverse Global South societies.Paper type Conceptual paper